PENDIDIKAN KARAKTER ANAK USIA DINI MODEL BEYOND CENTRE AND CIRCLE TIME - Nurlia Alfianti; Nada Shofa Lubis (stit-islamic-village, 2021)
This study aims to analyze early childhood character education through the Beyond Center and Circle Time model. This research is in the form of a literature review, carried out by collecting and analyzing data in the form of books; journal; website; articles and the Law of the Republic of Indonesia relating to the center learning model for early childhood character education. Meanwhile, the analysis of these data is carried out by using the content analysis method. The results showed that character education could be carried out appropriately through the center learning model (BCCT). This can be seen from the center learning process that emphasizes character values.